In this Way we will Some Day Overtake and Leave Behind the Estonians - Norkus, Zenonas (Problemos, 2002)
Baranova, Jūratė (Ed.) Lithuanian Philosophy: Persons and Ideas. Lithuanian Philosophical Studies, II. Washington: The Council for Research in Values and Philosophy, 2000 (Cultural Heritage and Contemporary Change. Series IVA. Eastern and Central Europe, Vol. 17. General Editor George F. McLean). XII +314 p.